If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -3 = 4(2x + -3) Reorder the terms: -3 + 8x = 4(2x + -3) Reorder the terms: -3 + 8x = 4(-3 + 2x) -3 + 8x = (-3 * 4 + 2x * 4) -3 + 8x = (-12 + 8x) Add '-8x' to each side of the equation. -3 + 8x + -8x = -12 + 8x + -8x Combine like terms: 8x + -8x = 0 -3 + 0 = -12 + 8x + -8x -3 = -12 + 8x + -8x Combine like terms: 8x + -8x = 0 -3 = -12 + 0 -3 = -12 Solving -3 = -12 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| (2y+7)(2y+7)=49 | | -(2z+2)+3(2z+4)-2z= | | 3+y+2y+y(2)+5+y= | | 3x^2-7xy+4y^2=0 | | x(x-11)+28=0 | | -3=2-.25k | | x^2-10+50=0 | | 4(3-3x)(8-2x^2)=0 | | (a-15)(2a+3)=0 | | 2.5(3x-9)-3(0.5x+4.5)=0 | | -10pb+9p=12 | | 3y+2y+y(2)+5+y= | | 5y-(2-y)=22 | | -10(-2x+1)= | | -2(c-9)-7(c+2)= | | .12x-.03(4-6x)=.02(x-2)-.04 | | -11-z=5 | | .5(3g-2)=6g | | 4u=-10+3u | | -11-2=5 | | 39-79d-95-5d+10+3d= | | 6+11x=60 | | y^3+3y^2-16y-48=0 | | y^3+3y^2=16y+48 | | 7e^5x=9e^6x | | 32y^2-18=0 | | 68x=51x+612 | | 3(h-4)=-0.5(24-6h) | | 3(h-4)=(24-6h) | | 51+17= | | -y+5-7=2y+6+3y | | (b+1)(b-6)=b-15 |